Cerebral Arterial and Venous Air Embolism Following Removal of Percutaneous Sheath Introducer - Sana Ghalib; Biplab K. Saha; Hau Chieng; Scott H. Beegle (Prague Medical Report, 2024)
Cerebral air embolism after removal of central venous catheter (CVC) is a rare complication but can lead to fatal outcomes. We report a rare case of both cerebral venous and arterial embolism occurring in a patient with underlying scleroderma-related interstitial lung disease (SSc-ILD) and pulmonary hypertension following removal of percutaneous introducer sheath for pulmonary artery catheterization. We discuss the mechanisms, pathophysiology, management and prevention of cerebral air embolism.